2017
DOI: 10.3390/md15100331
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Toxin Production and Allelopathic Effects of Pseudo-nitzschia multiseries under Iron-Enriched Conditions

Abstract: In order to assess the effects of Fe-enrichment on the growth and domoic acid (DA) production of the toxigenic diatom Pseudo-nitzschia multiseries, static cultures that received the addition of different iron (Fe) concentrations were maintained for 30 days. Intra- and extracellular DA concentrations were evaluated over time, and growth and chain-formation were compared to those of non-toxic diatoms, Bacillaria sp. Growth rates of P. multiseries (μ = 0.45–0.73 d−1) were similar among cultures containing differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Other studies suggest that DA synthesis requires available Fe (e.g. Sobrinho et al 2017). In both cases, accumulated iron in the polysaccharidic matrix of P.…”
Section: Da Implications In the Ecosystem And Challenges For Future Smentioning
confidence: 88%
“…Other studies suggest that DA synthesis requires available Fe (e.g. Sobrinho et al 2017). In both cases, accumulated iron in the polysaccharidic matrix of P.…”
Section: Da Implications In the Ecosystem And Challenges For Future Smentioning
confidence: 88%
“…They are, however, consistent with observations for DA producing Pseudo-nitzschia species. Even though an increased release of dDA in iron limited treatments was observed, exponential phase growth rates remained lower for these treatments than for iron sufficient treatments (Maldonado et al, 2002;Sobrinho et al, 2017).…”
Section: Effects Of the Experimental Conditions On Growth Size And mentioning
confidence: 82%
“…Since Pseudo-nitzschia spp. generally adapt well to low iron concentrations (Marchetti et al, 2006;Sobrinho et al, 2017), the limiting effect of iron might be relatively low in this experiment, resulting in changes less prominent. With regard to DA addition, elevated Fe:C was observable in the +DA treatment but not in the +FeDA treatment, which showed equally low values as in the Control treatment.…”
Section: Uptake and Potential Effects Of Domoic Acid On Cellular Metamentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, cells may be more vulnerable during sexual reproduction, so domoic acid could act as a grazer deterrent: its production has been shown to increase in the presence of copepods (Harðard ottir et al 2015. Finally, different studies also showed an allelopathic effect of Pseudo-nitzschia or DA addition on different phytoplankton species (Lundholm et al 2005, Smeti et al 2015, Sobrinho et al 2017, Van Meerssche et al 2018). Higher DA production may therefore also represent an ecological advantage that could offset the growth arrest/decrease during sexual events in Pseudo-nitzschia blooms.…”
Section: Discussionmentioning
confidence: 99%